Designing GeoGebra-Supported Instruction on Systems of Two-Variable Inequalities in Vocational High Schools under the Kurikulum Merdeka Framework - Desvi Astutiana; Erviani Fajri; Geby Fitrya Adrian; Desi Engriani; Lichia Rahmat; Zelhendri Zen (Journal of General Education and Humanities, 2026)
The Merdeka Curriculum emphasises student-centred, contextual, and problem-based mathematics learning, including in Vocational High Schools (SMKs). One of the key competencies in phase E is the ability to represent and interpret Two-Variable Linear Inequality systems, which requires mastery of both algebraic and graphical representations in an integrated manner. Recent studies indicate that integrating GeoGebra can enhance students’ conceptual understanding, motivation, and mathematical literacy across various algebra and geometry topics. However, instructional designs that specifically guide the use of GeoGebra for the Two-Variable Linear Inequality systems in SMK within the Merdeka Curriculum context remain limited. This article aims to develop a framework for designing GeoGebra-assisted learning of Two-Variable Linear Inequality systems for Grade X SMK students. The approach employed is a targeted literature review of the implementation of GeoGebra in mathematics learning from 2017–2025, combined with an analysis of the Merdeka Curriculum Learning Outcomes and Learning Objectives, and a study of student worksheets (LKS) featuring a series of GeoGebra activities designed by the authors. The review results in a set of design principles, including: the use of dynamic visuals to bridge symbolic and graphical representations, sequencing worksheets from guided exploration to vocational problem-solving, and integrating formative assessments based on screenshots and student reflections in GeoGebra. This framework is expected to serve as a reference for SMK teachers in designing more meaningful Two-Variable Linear Inequality system lessons aligned with the Merdeka Curriculum, while also opening avenues for further empirical research on the effectiveness of the proposed design.